Winter as a Source of Economic Growth - Mayarenkov, Sergey (project baikal, 2020)
The article considers the potential of the territories located in a cold climate zone. The author outlines the issues that can become a “growing point” for such territories, as well as the direction of theoretical studies for implementation of practical measures. The investment attractiveness of “winter” cities and Irkutsk in particular is highlighted.